Publiek, Republiek en die publieke kerk - Van der Merwe, IJ (Nederduitse Gereformeerde Teologiese Tydskrif, 2008)
Public, Republic and the public church A fundamental conviction of public theology, Stackhouse reminds us, is that the public (civil society) precedes the Republic (the state). In this article the author investigates the reality of a self-conscious pluralistic society and the reality of a self-conscious civil society from the perspective of the so-called “Böckenförde” dilemma that “the state lives from sources that it cannot guarantee itself”. The author argues that both pluralism and civil society should be welcomed by the public church and that the public church should partake in civil society as a community among communities, an ethos community which contributes to value consensus in the public sphere.